Hormonal induction of flounder Paralichthys adspersus (Steindachner, 1867) and spawning quality by laboratory conditions - Carrera, Lili (2022)
The aim of this objective study was to induce the spawning of mature females of Paralichthys asdpersus (sole) using a hormone analogue to gonadotropin (GnRHa) and to determine the quality of eggs and larvae obtained in the periods of 2014 and 2015. Females with oocytes were selected in advanced maturation (542.61 µm), which spawned after a latency period of 45-48 h at a temperature of 16.46 ± 0.06 °C. The percentage of fertilization was greater than 70% in both periods. The fertilized eggs had a diameter of 857.98 ± 5.90 µm and the oily droplet of 168.76 ± 5.31 µm. Hatching occurred 48 hours after spawning at 18.03 ± 0.13 °C, with percentages between 16.7 and 94.0% for both periods. For larval quality, the Larval Survival Index (ISL) was determined, where the larvae survived starvation for up to 11 days. The highest ISL value was 31.2% in 2014 and 22.9% in 2015. The accumulated mortality at day 3 (MA3) was higher in December 2014 (21.1%) and in April 2015 (13.7%). The proximal composition of eggs was 47.1% protein, 17.4% lipids and 3.9% carbohydrates. Fatty acids (mg/g of dry sample) show a predominance of polyunsaturated fatty acids, followed by saturated and monounsaturated fatty acids. DHA (docosahexaenoic acid, 22: 6n-3) was the most abundant of the polyunsaturated, followed by EPA (eicosapentaenoic acid, 20: 5n-3) and ARA (arachidonic acid 20: 4n-6). The DHA: EPA ratio was 3.4 ± 0.5. It is concluded that hormonal induction with GnRHa can produce quality eggs and larvae, however, it is necessary to consider a species specific diet for brodstock that can ensure good quality of the progeny.